Micro-LED with red-green-blue super-pixel integration for simultaneous display and optical near field communication - Liu, Xinyi; Wang, Li; Zhang, Chongyun; Liu, Chuanbiao; Lv, Zhijian; Liu, Zhaojun; Patrick Yue, C. (Optics express, 2022)
This work presents a novel all-in-one Micro-LED pixel (µLEDP) technology by integrating red-green-blue super-pixels (RGBSP) in a single unit cell. Measurement results show that the proposed µLEDP delivers excellent optical and electrical characteristics, including wide color gamut (109% NTSC), wide correlated color temperature range (2831.7-10016.8 K), and high modulation system bandwidth (58-62 MHz). To the best of our knowledge, the proposed integrated µLEDP achieves the highest data rate compared to published results based on other multi-color low-capacitance high-bandwidth LEDs. The maximum simulated non-return-to-zero (NRZ) and 4-level pulse-amplitude-modulation (PAM-4) data rates of 0.3-Gb/s and 1.1-Gb/s, respectively.